Law at, to or from the centre? The European Court of Justice and the harmonization of private law in the European Union - Johnston, A; Unberath, H (Oxford University Press, 2006)
In the European Union, making use of Directives as legislative instruments plays no small part for the harmonization of private law since they encompass the interaction between several different actors at both the Community and national level. Unlike Regulations that automatically entail direct effects, Directives — that are addressed to Member States and allow the Member States to decide which option to take in achieving the predetermined goal — have to be transposed into national law. While Community institutions are conventionally provided with the option of legislating through either Regulations or Directives, the latter amounts to lesser interference with the national system. By the principle of subsidiarity, and through observing past intents of imposing harmonization, Directives should thus be given first priority. This chapter looks into how Directives aid in achieving harmonization in private law.